2017
DOI: 10.2174/1874364101711010017
|View full text |Cite
|
Sign up to set email alerts
|

Macular Evaluation wıth Spectral Domain Type Optic Coherence Tomography in Eyes with Acute Nonarteritic Ischemic Optic Neuropathy at the Presentation Visit

Abstract: Purpose:To evaluate the macula with spectral domain type optic coherence tomography (OCT) in eyes with acute nonarteritic anterior ischemic optic neuropathy (NAION) at the presentation visit.Methods:Medical charts of the 133 patients who received the diagnosis of acute NAION between January 2008 and July 2014 at the Neuro-ophthalmology unit of Dokuz Eylul University were reviewed retrospectively. Sixtythree patients within 30 days of symptom onset with available baseline spectral domain type macular OCT were i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 19 publications
(21 reference statements)
0
9
0
Order By: Relevance
“…Subsequent case reports by others have also described submacular fluid in NAION patients, who notably appeared to respond well to systemic corticosteroid treatment (2,3). A recent study by Donmez et al showed that 34.9% of 63 NAION patients had some evidence of subretinal fluid on macular OCT obtained during their initial evaluation, with 23.8% (15 patients) having subfoveal fluid (5). In the present study, we have continued to observe subretinal fluid in a majority of cases (64% of eyes, 70% of patients).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Subsequent case reports by others have also described submacular fluid in NAION patients, who notably appeared to respond well to systemic corticosteroid treatment (2,3). A recent study by Donmez et al showed that 34.9% of 63 NAION patients had some evidence of subretinal fluid on macular OCT obtained during their initial evaluation, with 23.8% (15 patients) having subfoveal fluid (5). In the present study, we have continued to observe subretinal fluid in a majority of cases (64% of eyes, 70% of patients).…”
Section: Discussionmentioning
confidence: 99%
“…A recent article investigating OCT scans of the macula in the acute phase of NAION reported the novel finding of HRD in the outer retina in 15% of eyes (5). In the present study, we found that 44% of eyes had evidence of hyperreflective material, suggesting that HRD might be a phenomenon that has been overlooked to date.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…On the other hand, multiple groups have analyzed macular fluid in eyes with acute AION with variable prevalence and distribution across the different retinal layers. 16 , 24–26 …”
Section: Introductionmentioning
confidence: 99%